Myopia-related optic disc and retinal changes in adolescent children from singapore - Samarawickrama, Chameen; Mitchell, Paul; Tong, Louis; Gazzard, Gus; Lim, Laurence; Wong, Tien-Yin; Saw, Seang-Mei (Ophthalmology (Rochester, Minn.), 2011)
To examine early myopia-related optic disc and retinal changes in a Singapore Chinese adolescent sample without confounding ocular or systemic disease. Population-based cross-sectional study. Children aged 12 to 16 years at a follow-up visit for Singapore Cohort Study of Risk Factors for Myopia. Detailed eye examinations, including cycloplegic autorefraction and contact biometry, were performed. Retinal photographs were acquired using nonmydriatic retinal photography among children who attended follow-up examinations in 2006, and were graded for myopia-related optic disc signs and macular changes by a single experienced grader. Optic nerve head parameters were measured adjusting for camera and ocular magnification with appropriate formulae. Optic disc changes (tilt, beta peripapillary atrophy [β-PPA], and optic nerve parameters) and macular changes (staphyloma, lacquer cracks, Fuchs' spot, and chorioretinal atrophy). Retinal photography data were available for 1227 children (median age, 14 years; range 12-16). Tilted optic discs were found in 454 subjects (37%), and were associated with myopic spherical equivalent refractions (-3.6 diopters [D] vs -1.3 D; P<0.0001), higher cylindrical error (0.9 vs 0.7 D; P = 0.0001) and longer axial length (24.93 vs 23.96 mm; P<0.0001). The pattern of distribution of the axes of the tilted discs and corneal curvature were similar (P = 0.4). All linear optic nerve parameters, except vertical disc diameter (P = 0.15), were significantly smaller in eyes with than without tilted discs (P <0.001) after adjusting for confounders. Apart from 20 cases, all eyes with tilted optic discs had associated β-PPA. We identified only 1 case each (0.1% prevalence) of staphyloma and lacquer cracks in this sample. In this Asian adolescent population, tilted optic discs were highly prevalent, in contrast with the lower prevalence reported in Caucasian populations. Eyes with tilted discs tended to have smaller optic cups with smaller cup-to-disc ratios, and were associated with myopic refraction, higher astigmatism, and longer axial length. There were similar patterns of distribution between the axis of disc tilt and the axis of corneal curvature, which could have embryologic origins. In contrast with optic disc changes, myopic macular changes were rare in this age group, suggesting that these changes may develop later in life. The authors have no proprietary or commercial interest in any of the materials discussed in this article.